2012
DOI: 10.1007/s00540-012-1339-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jaw thrust and cricoid pressure maneuvers on glottic visualization during GlideScope videolaryngoscopy

Abstract: The jaw thrust maneuver was superior to videolaryngoscopy alone in improving the modified C&L grade and the visualized glottic area; however, no significant improvement was noted with cricoid pressure. We therefore recommend the use of jaw thrust as a first-line maneuver to aid in glottic visualization and tracheal intubation during GlideScope videolaryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Corda et al (11) showed that there was no statistically significant difference in glottis grade (39% of glottis grade improved and 20% worsened) when using GlideScope under cricoid pressure in 100 patients. However, it significantly decreased the glottis area by forcing vocal cord apposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corda et al (11) showed that there was no statistically significant difference in glottis grade (39% of glottis grade improved and 20% worsened) when using GlideScope under cricoid pressure in 100 patients. However, it significantly decreased the glottis area by forcing vocal cord apposition.…”
Section: Discussionmentioning
confidence: 99%
“…From data by Corda et al (11) and to detect a 20% worsened Cormack-Lehane grade and a 90% power with a=0.05, we calculated our sample size to be 29 per group (a total of 87 for the three groups). Then, we decided to enrol 40 patients per group (a total of 120) with consideration of possible exclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Several measures are suggested as predictors of difficult airway namely short TMD, limited mouth opening, and head extension (15)(16)(17)(18). Expectedly, the current study patients with these predictors got higher Cormack-Lehane scores.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a pre-curved specific stylet compatible with the 60º curve of GlideScope blade must be used and both advancement of tracheal tube and withdrawal of the stylet after intubation may cause a stimuli to the anterior commissure or anterior wall of trachea. [31] Xue et al [20] studied the GlideScope and Macintosh laryngoscopes in ASA I patients and did not found significant advantage in terms of hemodynamic response to endotracheal intubation, while intubation time was significantly higher in the GlideScope group. They claimed that the manipulation of GlideScope stylet, may cause higher stimulus to the larynx and trachea, counterbalancing the lower upward lifting force required for laryngoscopy.…”
Section: Macintoshmentioning
confidence: 99%